Factors Associated With Presenteeism in Female Workers: A Cross-Sectional Study - Luthfia Zalfa Kamilina; Chahya Kharin Herbawani; Een Kurnaesih; Suparni (Jurnal Ilmu Kesehatan Masyarakat, 2025)
The prevalence of presenteeism among female employees is higher than among male workers due to greater pressure to perform. This condition can lead to musculoskeletal pain, poor mental health, sleep difficulties, depression, and burnout. This study aimed to analyze the association between individual factors and work-related factors with presenteeism behavior among female workers at PT Bank BNI. The study used a cross-sectional study design with a population of 110 female workers. The sampling technique used a saturated sampling technique with the entire population as the sample. Data were collected through online questionnaires of individual characteristics questionnaires, Questionnaire for the Experience and Evaluation of Work (QEEW), job insecurity questionnaires, Co-Worker Support Scale questionnaires, and SPS-6 questionnaires. Data analysis included univariate, bivariate, and multivariate. Bivariate analysis used the chi-square test and simple logistic regression test, while multivariate analysis used multiple logistic regression tests. The univariate analysis showed that 73,6% of respondents exhibited high levels of presenteeism. Bivariate analysis indicated a significant association between age, marital status, and tenure (p-value < 0.05) with presenteeism. Multivariate analysis identified education level as the most dominant variable (POR = 4.847). This study concluded that younger age, married status, and shorter tenure influence presenteeism behavior among female workers at PT Bank BNI, with higher education level as the dominant variable. Therefore, companies should consider providing training or workshops on presenteeism and implementing paid sick leave policies to prevent presenteeism behavior and increase work productivity.